Testing the mechanical performance of a single taper-retained implant–abutment connection under static and dynamic loads: an in vitro study - Wu, Hao; Cao, Ning; Cao, Liang-Wei; Guo, Shui-Gen; Zhang, Xu; Yu, Fei; Wei, Shi-Bo; Wei, Hong-Wu (Frontiers in Materials, 2025)
The mechanical strength and stability of single taper-retained implant–abutment connections in dental implantations have not been determined. We evaluated the mechanical performance of a single taper-retained implant system with two specifications (M1 and M2, with locking diameters being 2.0 and 2.5 mm, respectively). Static and dynamic loading, torsional strength, and lateral load tests were performed. M1 and M2 samples showed significantly different (P < 0.05) static destructive powers (363.3 ± 22.32 and 583.6 ± 15.7 N, respectively). The dynamic maximum bending moment of both samples was 1276 N mm. M1 and M2 samples showed a yield torque of 114.8 ± 13.9 and 114.3 ± 6.9 N cm, a maximum yield torque of 130.0 ± 12.0 and 156.5 ± 6.6 N cm (P < 0.05), an axial pull force of 179.8 ± 19.5 and 207.4 ± 13.7 N (P < 0.05), and a lateral force of 140.2 ± 14.7 N and 238.15 ± 14.38 N (P < 0.05). No damage or fracture was observed in abutments or implants after testing. The single taper-retained implant–abutment connection showed high mechanical stability and durability, thus is a reliable replacement of the traditional screw-retained connection. Increasing the locking diameter of the abutment enhanced the mechanical strength of the connection.